Note on a Marshallian Conjecture - Kemp, Murray C. (Quarterly Journal of Economics, 1966)
Journal Article Note on a Marshallian Conjecture Get access Murray C. Kemp Murray C. Kemp University op New South Wales Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 80, Issue 3, August 1966, Pages 481–484, https://doi.org/10.2307/1880734 Published: 01 August 1966